The influence of green human resource management and green innovation on business sustainability mediated by digital skills at RSUD sayang cianjur - Ainayah, Ainayah; Setyaningrum, Retno Purwani (Institute of Computer Science (IOCS), 2024)
Competition between companies is increasing, therefore company characteristics that can invite competitiveness between competitors are very much needed. The aim of this research is to determine the direct and indirect influence between the variables green human resource management and green innovation mediated by digital skills on business sustainability. This research was conducted using a quantitative approach, where the respondents were health workers at RSUD Sayang Cianjur with a population of 1,413 people and a sample of 93 people. Data collected from health workers in the form of a statement questionnaire that represents the information needed in the study to obtain a number of data or information relevant to the research topic. The analytical method used in this research is Partial Least Square (PLS) using the SmartPLS version 3.0 program. The research results show that green human resource management has a positive influence on business sustainability, green innovation have no influence on business sustainability, digital skills has a positive influence on business sustainability, green human resource management has an influence on digital skills, green innovation have no influence on digital skills, green human resource management mediated by digital skills has on influence on business sustainability, and green innovation mediated by digital skills has no influence on business sustainability